How we can use JF standard for Japanese language education in al-Farabi Kazakh national university - Bakhautdinova, G. N. (Journal of Oriental Studies, 2016)
In this paper we can see explanation of JF standard for Japanese language education and how we can apply and implement it in al-Farabi Kazakh national university.